THE EFFECT OF PHYSICAL ACTIVITY AND HEALTHY LIFESTYLE FOR HOUSEWIVES AGAINST CHILDREN'S BEHAVIORAL TENDENCIES - Zuraidah Zuraidah; Rahma Dewi (Indonesia Sport Journal, 2021)
This study aims to determine the correlation between the application of physical activity and healthy lifestyle of housewives to the tendency of children's behavior. The research sample was 30 housewives in Lenggadai Hilir Village. They are mothers who have children at the level of early childhood education to high school. The research method is descriptive qualitative. Collecting data with a closed questionnaire. The results showed that the percentage of the value was still low, namely 51.5%, so the researchers could conclude that most of the housewives had not carried out physical activity and implemented a healthy lifestyle properly. Mother considers all the activities that she does only as a necessity that is her personal responsibility without involving all family members and still does not know the greater benefits of physical activity and a healthy lifestyle and its influence on children's behavior.Keywords: Activity, Healthy Lifestyle, Housewife, Child Behavior